PERLINDUNGAN TERHADAP KONSUMEN KORBAN SKEMA PONZI OLEH PENYELENGGARA PERDAGANGAN MELALUI SISTEM ELEKTRONIK (PPMSE) JOMBINGO - Nadirra Maharani Putri (2024)
The direction of technological advancement impacts not only the development of information and electronics but also lifestyle changes, including economic activities. Jombingo, as an Penyelenggara Perdagangan Perdagangan Melalui Sistem Elektronik (PPMSE) admired by society, violates Article 4 paragraph (3) of UU Perlindungan Konsumen No. 8 tahun 1999 regarding consumers' rights to accurate, clear, and honest information by offering investment products without the permission of the Otoritas Jasa Keuangan (OJK) and causing material losses to consumers. The core issue of this research is (1) How is consumer protection against the losses caused by the Penyelenggara Perdagangan Perdagangan Melalui Sistem Elektronik (PPMSE) Jombingo?; (2) What legal actions can consumers take when experiencing losses due to the Penyelenggara Perdagangan Perdagangan Melalui Sistem Elektronik (PPMSE) Jombingo? To address these issues, a normative juridical study was conducted using secondary data as the primary information related to the research object and analyzed descriptively qualitatively. The conclusions drawn from this research are: (1) UU Perlindungan Konsumen regulates that businesses violating consumer protection provisions may face sanctions such as revocation of business licenses, and consumers can seek dispute resolution both outside and through the court; (2) As stipulated in Article 1496 of the KUH Perdata, consumers experiencing losses can file civil lawsuits for compensation, interest, litigation costs, or money return for unfulfilled promises made. Criminal regulations regarding compensation can be pursued through resistusi and compensation requests; consumers can also request compensation through out-of-court discussions via conciliation, mediation, and arbitration.